A DESCRIPTIVE ANALYSIS ON QUASI-LEGAL LANGUAGE IN LEASE CONTRACTS - ANGI, AYŞEGÜL (My University, 2020)
Despite the high frequency of the specific field translation, there are considerably few studies on thetranslation of the non-literary (non-fictional) texts. Accordingly, this study was pursued to elaborate onespecific legal genre, namely lease contracts, by describing its textually-defined linguistic units within thelexical and syntactic framework. Upon analysing a limited corpus of Turkish leasing contracts (as sourcetexts) and those of English (as source and target texts), it has been found out that like other similar legaltexts, they embrace such impartial usages as the gender-neutral pronouns and conspicuously stated commonnouns. Unlike the other normative texts, these lease contracts include shorter sentences and few archaicwords and structures, and active voice rather than passive voice is used in the verbs of their main clauses.When contrasting with the other legally enforceable texts, these textually-defined linguistic units of the corpus can be associated with a plain language usage; thus, it can be stated that a quasi-legal language is used inthese lease contracts. Obviously, by virtue of this quasi-legal language, all the parties with different educational,economic, and cultural backgrounds as well as having different levels of experience and knowledge on leasingmay comprehend the contractual terms much more easily.

Yaygın bir şekilde özel alan çevirisi yapılmasına rağmen edebi metinlerin dışındaki metinlerin çevirileri_x000D_ ile ilgili yapılan araştırmaların sayısı oldukça azdır. Edebi metinlerin dışında ve bir hukuk metin türü olarak_x000D_ sınıflandırılan kira sözleşmelerinin metin dilbilimsel betimlenmesi, sözcük ve söz dizimi çerçevesinde bu_x000D_ çalışmada ele alınmıştır. Bütünce, Türkçe (kaynak metin olarak) ve İngilizce (kaynak metin ve erek metin_x000D_ olarak) hazırlanan sınırlı sayıdaki kira sözleşmelerinden oluşmaktadır. Bu metinler çözümlendiğinde,_x000D_ benzer hukuk metinlerinde olduğu gibi, kişisel olmayan zamirler ve belirgin bir üslupla yazılan cins_x000D_ isimleri gibi nesnel kullanımlara yer verildiği görülmektedir. Diğer normatif metinlerden farklı olarak, bu_x000D_ kira sözleşmelerinde daha kısa cümlelerin ve az sayıda eski kelime ve yapıların yer aldığı ve temel cümle_x000D_ fiillerinde edilgen yapıdan ziyade etken yapının kullanıldığı görülmektedir. Yasal olarak bağlayıcı olan diğer_x000D_ hukuk metin türleri kıyaslandığında, bütünce içerisinde yer alan kira sözleşmelerinin metin dilbilimsel_x000D_ özellikleri, daha sade, hukuk benzeri bir dil kullanıldığına da işaret etmektedir. Eğitim seviyeleri, ekonomik_x000D_ ve kültürel durumları ve kiralama konusundaki birikimleri birbirinden farklı olan sözleşme taraflarının,_x000D_ hukuk benzeri bir dil kullanılmasıyla sözleşme maddelerini daha kolay anlayacakları aşikardır.
KIRA SÖZLEŞMELERINDE KULLANILAN HUKUK BENZERI DILIN BETIMLEMELI ÇÖZÜMLENMESI